A168 KAISO-INDUCED INTESTINAL INFLAMMATION IS ACCOMPANIED BY FAULTY CELL ADHESION AND ABERRANT INTESTINAL REPAIR. (1st March 2018) - Robinson, S; Chaudhary, R; Jimenez-Saiz, R; Rayner, L; Jodana, M; Daniel, J
Abstract: Background: Kaiso is a member of the POZ-ZF family of transcription factors that play key roles in vertebrate development and disease. We previously reported that intestinal-specific overexpression of Kaiso ( Kaiso Tg ) potentiates Wnt-induced colon cancer and results in chronic inflammation in 1-year old mice. Notably, the intestines of Kaiso Tg mice exhibit phenotypes reminiscent of human IBD, including leukocyte infiltration, expanded crypts, and blunted villi. However the mechanism underlying Kaiso-induced inflammation was unknown. Aims: In this work, we seek to identify the factors/mechanisms predisposing Kaiso transgenic mice to subsequent intestinal inflammation. Methods: To assess morphological differences relative to non-transgenic (nonTg) mice, histological comparisons were performed using two independent Kaiso Tg mouse lines at 8-months of age. Flow cytometry was performed to ascertain differences in immune cell populations. We also performed myeloperoxidase (MPO) activity assays to assess neutrophil activity in Kaiso Tg mice. Immunohistochemistry (IHC) of cell adhesion proteins was used to determine differences in subcellular location, and western blot was used to quantify differences in their expression. IHC of Ki67 and western blot of Cyclin D1 were used to compare differences in proliferation. To assay in vivo collective cell migration, mice were given a single injection of BrdU and sacrificed 24- and 48-hours post injection. The distance migrated of BrdU-retaining cells was then quantified. Results: In this work, we show that Kaiso overexpression elicits a neutrophil-specific inflammatory response, as indicated by increased MPO activity, elevated mRNA expression of the neutrophil chemokine, MIP-2, and formation of crypt abscesses. To identify the factor(s) predisposing Kaiso Tg mice to subsequent inflammatory disease, subclinical (12-week old) mice were examined prior to the onset of inflammation. Notably, E-cadherin localization and expression were reduced in subclinical Kaiso Tg mice, thus weakening the intestinal barrier and predisposing the mice to subsequent inflammation. Subclinical Kaiso Tg mice also displayed abnormal intestinal renewal mechanisms, such as delayed proliferation and accelerated cell migration. Conclusions: Together, these findings demonstrate that a weakened intestinal barrier and irregular intestinal renewal mechanisms may play a role in the development of subsequent intestinal inflammation caused by Kaiso overexpression. Importantly, our findings may hold clinical significance, since Kaiso expression is elevated in colon cancer and some cases of Crohn's disease. Funding Agencies: CIHRNSERC